Infantile acute liver failure in the West of Scotland. Issue 8 (12th November 2019) - Wands, David; Tayler, Rachel; Kelly, Deirdre; Pinto, Fernando; Simpson, Judith Helen; Hansen, Richard
Abstract : Background: Our current understanding regarding the aetiology of infantile acute liver failure largely derives from studies conducted by regional liver units. This may introduce selection bias and therefore not provide a true reflection of the wider population. Methods: Every coagulation screen with a prothrombin time ≥18 s in our centre was examined over one calendar year. All patients less than 1 year of age were included and their electronic records retrospectively reviewed. Results: 24 patients were identified, from 9989 coagulation screens, that fit the current definition of acute liver failure. Hypoxic birth injury and ischaemic events were the most common aetiologies. Survival was 75%. Conclusion: The 'catch-all' methodology employed demonstrated that acute liver failure is more common than previously reported and suggests that current data may exclude large numbers who either have more minor self-resolving disease or conversely have severe disease leading to death prior to transfer.